Prevalence and prognosis of frailty in patients >70 years old with acute coronary syndrome referred to invasive angiography. (3rd May 2023) - Ratcovich, H; Palm, P; Faerch, J; Bang, L; Engstroem, T; Tilsted, H H; Holmvang, L
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Rigshospitalet Research Foundation Background: The number of older patients is increasing world-wide. Older patients have a higher risk of complications related to acute coronary syndrome (ACS) treatment and are more often frail. Yet, they are often missing in clinical trials, which leads to a knowledge gap in current guidelines when treating older ACS patients. Frailty scoring may be a better tool than conventional risk scores to assess prognosis. Previous studies have proposed that a patient's biological age instead of chronological age could be used to better guide the treatment strategy in older ACS patients. Potentially frailty scoring can be used to decide a patient's biological age. Purpose: We wanted to investigate the prevalence of frailty in a consecutive population of ACS patients ≥70 years referred to invasive angiography at a tertiary centre. Furthermore, we wanted to investigate whether frail patients had a worse 12-month outcome compared to non-frail patients. Methods: From September 2020 to September 2021 all patients ≥70 years referred to our institution with ACS were, when logistically possible, undergoing bedside frailty scoring using the clinical frailty scale (CFS). The CFS scoring was performed at the time of admission by nurses at the department. Patients were divided into three frailty groups depending on their CFS score: Robust (1-3), Vulnerable (4) and Frail (5-9). Patients were followed for 12 months. Results: During the study period, 691 patients ≥70 years old with ACS were admitted. Of the 451 (65%) patients who had a frailty assessment, 70 (16%) patients were frail, 77 (17%) were vulnerable and 304 (67%) were robust. Frail and vulnerable patients were older (frail: 80.9 (5.6) years, vulnerable: 78.5 (5.7) years and robust: 76.7 (4.8) years, p<0.001), had more comorbidities, defined as a higher Charlson index score (frail: 4.5 [4.0-5.0], vulnerable: 4.0 [4.0-6.0] and robust: 4.0 [3.0-4.0], p<0.001) and longer hospitalisation (frail: 5 [3-9.2] days, vulnerable: 8 [3.5-14.0] days and robust: 5 [3-7] days, p=0.021). Furthermore, frail and vulnerable patients less frequently underwent revascularisation during their first admission (frail: 58.9%, vulnerable: 65.1% and robust: 77.9%, p<0.001). In 12-month follow-up, frail and vulnerable patients had a higher cumulated incidence of all-cause mortality compared to robust patients (p<0.001), figure 1. Frail patients had more than four times the risk of 12-month all-cause mortality compared to robust patients (HR 4.16 (2.12-8.15), p<0.001). The association remained significant after adjustment for age and comorbidities (HR 2.71 (1.30-5.64), p=0.008), as well as for GRACE score (HR 2.98 (1.50-5.90), p=0.002), table 1. Conclusion: In patients ≥70 years old with ACS and referred to invasive angiography, frailty according to the CFS score had a prevalence of 16%. Frail and vulnerable patients had more than four times the risk of all-cause mortality in 12-month follow-up. Figure 1. Table 1.